Literature review of the cytotoxic activity of faloak (sterculia quaddrifida r.br) against t47d and mcf-7 breast cancer cells and its active compounds - Rumaldus Seran; Wiwin Herdwiani; Titik Sunarni (Institute of Computer Science (IOCS), 2026)
Faloak (Sterculia quadrifida R.Br) is one of the plants used by the community as a multipurpose drug. Faloak bark herb has long been used by the people of East Nusa Tenggara as a medicinal plant. Empirically, boiled water from the bark of the faloak plant is used by the people of East Nusa Tenggara as a cure for hepatitis, typhus, ulcers, and stamina recovery. The data extraction method used is narrative by grouping similar data from the literature review results according to the size of the results to be presented. The flow of the journal search is about testing the cytotoxic activity of faloak (Sterculia quadrifida R.Br) against T47D and MCF-7 breast cancer cells and the content of their active compounds. From these data, screening, journal eligibility, and monitoring of conformity with inclusion and exclusion criteria were carried out to obtain appropriate journals to conclude the cytotoxic activity of faloak. The results of a literature review showed that faloak (Sterculia quadrifida R.Br) had cytotoxic activity against T47D and MCF-7 breast cancer cells. Chemical compounds that have cytotoxic activity are alkaloids, flavonoids, terpenoids, tannins, naphthoquinone, apigenin, and puerarin. Naptaquinone derivatives 2,3-dihydro-6hydroxy-2-methylenenaphtho [1,2-b] furan-4,5-dione and 2-iminoethyl 2-(2-(1-hydroxypentan-2-yl) phenyl) acetate obtained from the extract or active fraction of faloak bark (Sterculia quadrifida R.Br) showed cytotoxic activity against T47D breast cancer cells. Apigenin compounds were found to be the most effective phytoestrogens in inhibiting the growth of breast cancer cells. Apigenin also has apoptotic effects and induces autophagy in breast cancer cells. an effective proteasome inhibitor in breast cancer cell culture and breast cancer xenografts, and puerarin can increase DUSP1 expression by increasing the expression level of miR-133a-3p in breast cancer cells.